TEACHER AUTHORITY IN SCHOOL - Jozauska, Kristine (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The purpose of education is to initiate the young into the different ways in which, over the centuries, men have organized their experience and understanding of the world. This initiation depends upon the ability of teacher to explain and inspire, and on the willingness of the young to engage in this enterprise with a proper humility. The discussion on the role of authority in knowledge development and the subject of lack of teacher's authority is in great tension. The role of the teacher has changed, authority, a fundamental part of the teaching–learning process, is a problematic and questioned by society, the media, parents and students. Due to the fact that the teacher is in the role of the manager of the class, they require power in another form, the authority to influence student behavior. This could be termed teacher authority. Power and authority are central features of teachers' work. Many studies of teachers emphasize the impact that teachers have on students. Legitimate teacher authority is fundamental to effective teaching, but is often a thorny issue that teachers need to grapple with when teaching in modern teaching contexts.The main goal of the article is to analyze the teacher's authority and the pedagogical act in the situation of social change.